Dampak hukum, lahan sawah dilind Dampak Hukum Keputusan Menteri Atr/Bpn Nomor 1589/Sk-Hk.02.01/Xii/2021 Tentang Lahan Sawah Dilindungi Terhadap Hak Milik Atas Tanah. - Wahyuddin Wahyuddin; Allan Mustafa Umami; Fatria Hikmatiar Al Qindy (Faculty of Law, Maranatha Christian University, 2023)
Land ownership rights are the strongest, fullest rights and can be defended by anyone. According to Law Number 5 of 1960 concerning Basic Regulations on Agrarian Principles, the state has the right to control. The government issued a regulation regarding protected rice fields which only determines the area of ​​rice fields for each region as determined by the Minister of Atr/Bpn Decree Number 1589/Sk-Hk.02.01/Xii/2021 concerning Protected Rice Fields without explaining in more detail the government's responsibilities towards the communities involved. The land is designated as a protected rice field. The formulation of the problem in this research are what is the impact and legal force of the Decree of the Minister of Atr/Bpn Number 1589/Sk-Hk.02.01/Xii/2021 have on land ownership rights. The objectives of this research are to determine the legal impact and the legal strength of the Decree of the Minister of Atr/Bpn Number 1589/Sk-Hk.02.01/Xii/2021 on land ownership rights. The research method in this study uses normative research methods, namely examining regulations and legal doctrine from legal experts. The results of this research, with the Decree of the Minister of Atr/Bpn Number 1589/Sk-Hk.02.01/Xii/2021, have resulted in the ownership rights to land affected by the designation of protected rice fields not being able to be fully utilized. Then the legal force of the Decree of the Minister of Atr/Bpn Number 1589/Sk-Hk.02.01/Xii/2021 concerning protected rice fields becomes less strong and irrelevant because the rules are unclear and conflict with higher regulations.